The scarcity value of Treasury collateral: Repo market effects of security-specific supply and demand factors - Stefania D'Amico; Roger Fan; Yuriy Kitsul (Federal Reserve Bank of Chicago, 2013)
In the repo market, forward agreements are security-specific (i.e., there are no deliverable substitutes), which makes it an ideal place to measure the value of fluctuations in a security's available supply. In this study, we quantify the scarcity value of Treasury collateral by estimating the impact of security-specific demand and supply factors on the repo rates of all the outstanding U.S. Treasury securities. Our results indicate the existence of an economically and statistically significant scarcity premium, especially for shorter-term securities. The estimated scarcity effect is quite persistent, seems to be reflected in the Treasury market prices, and could in part explain the flow-effects of the Fed's asset purchase programs. More generally, it provides additional evidence in favor of the scarcity channel of quantitative easing. These findings also suggest that, through the same mechanism, the Fed's reverse repo operations could help alleviate potential shortages of high-quality collateral.
Keywords: G1; G12; G19; C23; 330; Collateral; securities; repo market; treasury bonds